TRADISI NAUR DANDA DALAM SISTEM PERKAWINAN EKSOGAMI DI DESA ADAT GOBLEG KECAMATAN BANJAR KABUPATEN BULELENG (Perspektif Teologi Hindu) - anjani, ni ketut (Jurnal Ilmiah Dinamika Sosial, 2017)
ABSTRACTThe purpose of this research is to know and analyze the execution procession of tradition of naur danda in exogamy marriage system in Gobleg village of Banjar Subdistrict of Buleleng Regency. The research was conducted qualitatively. Data were collected through observation, interview and literature study. The tradition of naur danda in the exogamy marriage system in Gobleg Adat Village, Banjar Sub-district, Buleleng District, combines theories consisting of religious theories from Clifford Geertz theory from Robert K. Merton and the theory of symbols From Geertz.The result of the research shows that the theological meaning of the naur danda tradition in Eksogami Marriage in Gobleg Traditional Village is the meaning of worship of the god yadnya, rsi yadnya, pitra yadnya, manusa yadnya and bhuta yadnya or nature. But most importantly, the worship of the Betawi Ida of 39 manifestations that berstana at Pura Pemulungan Agung / Pura Desa, which is a combination of 33 temples and manifestations of God with different degrees and functions.Keywords: Tradition naur danda, Marriage, Religious and Traditional Village Gobleg.